Henry C. "Hank" Smith and the Cross B Ranch : The First Stock Operation on the South Plains - Sosebee, M. Scott, 1961- (Book collections on Project MUSE., 2021)
"In reality, not all, or even most, ranching operations in Texas and the American West reflected the "oversized" legend. Indeed, most ranch undertakings were small businesses made up of modest landholdings, thin herds, limited financial resources, and few employees. They struggled to survive, often did not, and as a result, are often overlooked in histories so often dominated by big business. Henry C. "Hank" Smith and the Cross B Ranch tells the story of one of those smaller but significant ranches and its owner. A somewhat reluctant rancher, Smith preferred raising sheep to driving cattle, and yet he was one of the first in West Texas to upgrade his stock with purebred bloodlines. He spent more time on foot than on horseback, preferred a broad brim hat over a Stetson, and probably thought of himself more as a gardener than a rancher. Even so, the Cross B Ranch of the Blanco Canyon, surrounded by big ranching empires, was quite successful. Historian M. Scott Sosebee offers a compelling and readable biography, exploring big ideas about the American West on the small stage of an unassuming ranch. "Henry C. "Hank" Smith and the Cross B Ranch" will be an important contribution to the new history of the American West"--Provided by publisher.